Implementation of the Deep Learning Approach in Civic Education to Enhance Students Democratic Literacy and Critical Thinking Attitudes - Iqbal Iqbal; Syafriadi Syafriadi; Ery Wati (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This study aims to analyze the implementation of the Deep Learning approach in Pancasila and Civic Education and to examine its effect on improving students’ democratic literacy and critical attitudes at SMP Negeri 1 Simpang Tiga. The research employed a quantitative approach with a One Group Pretest-Posttest Design, involving 30 Grade VIII students selected through purposive sampling technique. Data were collected using democratic literacy tests, critical attitude questionnaires, and observation sheets, then analyzed through descriptive quantitative methods, while the level of improvement was calculated using the N-Gain formula. The results indicate a significant increase, where the average score of students’ democratic literacy rose from 68.4 to 84.2, and the average score of critical attitudes increased from 65.7 to 82.6. This improvement occurred across all measured indicators, accompanied by greater student involvement and activeness during the learning process. Based on these findings, it can be concluded that the Deep Learning approach is proven effective in enhancing students’ democratic literacy and critical attitudes. This approach creates a meaningful, contextual, and student-centered learning process, making it highly relevant to support the implementation of the Independent Curriculum and the strengthening of the Pancasila Student Profile.